MODULE AS AN IMPORTANT FACTOR OF STUDENT'S INDEPENDENT WORK MANAGEMENT - Pirimjarov, M.Kh.; Aymanganbetov, M.N.; Mambetkadırov, G.A. (SCIENCE and SOCIETY, 2025)
This article discusses the development of module materials for independent education of students. Much attention is paid to the methodical function of the teacher when performing independent work of students.